Valuing Life. - Kleinig, John (Studies in moral, political, and legal philosophy., 2014)
Abortion, euthanasia, capital punishment, war, genetic engineering and fetal experimentation, environmental and animal rights--these topics inspire some of today's most heated public controversies. And it is fashionable to pursue these debates in terms of the negative query ""Under what conditions may life be disregarded or terminated?"" John Kleinig asks a different, more positive question: What may be said in behalf of life? Looking at the full range of appeals to life's value, he considers a variety of issues. Is livingness as such to be affirmed and respected? Is there an ascending orde.